Utilization of Accounting Information System (SIA) in Optimizing Company Financial Statements - Chandra, Aditya Kurniawan; Kanivia, Aan; Fahrudin, Rifqi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The development of information technology has significantly affected the company's Accounting Information System (SIA), especially data processing moving from manual to computerized. The purpose of this article is to find out the use of Accounting Information Systems to Optimize the Company's Financial Statements by using the Systematic Literature Review (SLR) method to synthesize the findings of studies related to the use of SIA in optimizing the company's financial statements. The results of the study show that SIA plays a role as a tool to facilitate company activities and improve the quality of financial statements. The close relationship between information technology and SIA makes a positive contribution to the effectiveness of planning, control, analysis, decision-making, and presentation of financial statements. The benefits of SIA include transparency of business data, function as a comprehensive decision-making system, and the development of a systematic internal control system. In the competitive era, companies need to continue to make technological changes to increase their competitive advantage through the use of SIA.